Unseating Mastery: The University and the Promise of the New - Hörl, Erich; Lalu, Premesh (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
The conversation between Erich Hörl and Premesh Lalu draws on their extended conversation on efforts to link discordant temporal and spatial encounters with the idea of the university and how, more importantly, to care for the future of its educational responsibilities. While much of the debate on the university is focused on how it is affected by large-scale geopolitical shifts and the rapid expansion of technological resources, Hörl and Lalu bring into view a language of the university that holds to its promise in the sources of a founding supplement that may yet exhibit the potential for guiding the university through turbulent times ahead. This is a call for a retracing of the emergence of the complex hegemony of the master signifier in university discourse, and the potential to supersede it by way of a re-articulation of the desire for a concept of freedom borne out of the emancipation of the 19th-century institution of slavery.
Keywords: Futurity; Higher Education; Post-Apartheid; University Discourse